1997
DOI: 10.1017/s1041610297004523
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Phenomenological Comparison of Complex Visual Hallucinations in Dementia With Lewy Bodies and Alzheimer's Disease

Abstract: Visual hallucinations (VH) are a core feature of dementia with Lewy bodies (DLB), but little is known about their phenomenology. A total of 73 dementia patients (42 DLB, 30 Alzheimer's disease [AD], 1 undiagnosed) in contact with clinical services were assessed with a detailed standardized inventory. DLB was diagnosed according to the criteria of McKeith and colleagues, AD was diagnosed using the NINCDSADRDA criteria. Autopsy confirmation has been obtained when possible. VH were defined using the definition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 12 publications
(19 reference statements)
1
51
0
Order By: Relevance
“…1 A range of neuropsychiatric symptoms such as hallucinations, delusions, and sleep disturbances occur more frequently in DLB patients than in Alzheimer's disease patients from the early stages of the disease. [2][3][4][5] It has been suggested that caring for patients with DLB leads to a heavier caregiver burden than caring for those with Alzheimer's disease because of the involvement of neuropsychiatric symptoms such as delusions and hallucinations. [6][7][8][9] Therefore, the management of neuropsychiatric symptoms is a significant issue for maintaining the quality of life of patients with DLB and their caregivers.…”
mentioning
confidence: 99%
“…1 A range of neuropsychiatric symptoms such as hallucinations, delusions, and sleep disturbances occur more frequently in DLB patients than in Alzheimer's disease patients from the early stages of the disease. [2][3][4][5] It has been suggested that caring for patients with DLB leads to a heavier caregiver burden than caring for those with Alzheimer's disease because of the involvement of neuropsychiatric symptoms such as delusions and hallucinations. [6][7][8][9] Therefore, the management of neuropsychiatric symptoms is a significant issue for maintaining the quality of life of patients with DLB and their caregivers.…”
mentioning
confidence: 99%
“…On the other hand, the basis of the AD diagnostic criteria for DSM-IV-TR [6] and NINCS-ADRDA [7] is to exclude nervous system diseases that cause progressive dementia, which is not always easy in practice. Symptoms, except for dementia, are key factors in the discrimination of these diseases, but a total of 93% of DLB patients and 27% of AD patients are reported to have experienced visual hallucination [8]. Retrospective analysis of AD or DLB, confirmed at necropsy, detected fluctuation of mental symptoms not only in DLB (90%) but also in AD (5%) [9].…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective analysis of AD or DLB, confirmed at necropsy, detected fluctuation of mental symptoms not only in DLB (90%) but also in AD (5%) [9]. Visual hallucinations were common in DLB (80%) and not rare in AD (19%), whereas auditory hallucinations, frequent in DLB (45%), were not present in AD (0%) [8]. Extrapyramidal signs could be absent in 29% of autopsy-verified DLB [10] but were seen in 31% of the AD patients without α-synuclein deposits [11].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comes to the similar conclusion that patients with signifi cant tangle pathology who are pathologically assigned a DLB diagnosis were clinically indistinguishable from AD [26] . On the other hand, there are authors who report that visual hallucinations are more common in DLB [27,28] and suggest that the distinction between AD and DLB may be improved by greater emphasis on hallucinations [29] . Furthermore, some studies found a signifi cantly higher impairment of attention in patients with DLB [30] and more fl uctuations of attention compared with patients who suffered from AD [31,32] .…”
Section: Discussionmentioning
confidence: 99%